1998
DOI: 10.1023/a:1024880713245
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: This study investigates political communication as a mediator of the socializing effects of major political events. We earlier found that presidential campaigns are occasions for increased crystallization of partisan attitudes among adolescents (Sears and Valentino, 1997). But what drives the socialization process during the campaign? Either the campaign saturates the media environment with political information, socializing all adolescents roughly equally, or greater individual exposure to political informati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(14 citation statements)
references
References 129 publications
0
13
0
1
Order By: Relevance
“…In this way, researchers have shown that "if parents are politically engaged and frequently discuss politics with the child, transmission rates rise substantially, particularly on topics of general political significance and salience" (Jennings et al, 2009). Here, regular political events, as well as more episodic events, offer socialization opportunities for parents (Valentino and Sears, 1998).…”
Section: Political Attitudes Of the Youthmentioning
confidence: 99%
“…In this way, researchers have shown that "if parents are politically engaged and frequently discuss politics with the child, transmission rates rise substantially, particularly on topics of general political significance and salience" (Jennings et al, 2009). Here, regular political events, as well as more episodic events, offer socialization opportunities for parents (Valentino and Sears, 1998).…”
Section: Political Attitudes Of the Youthmentioning
confidence: 99%
“…Thus, parents are perceived as the principal agent of socialization in childhood. For example, in political or religious socialization research, parental attitudes have repeatedly been found to be main determinants of offspring attitudes (e.g., Dalhouse & Frideres, 1996;Glass, Bengston, & Dunham, 1986;Granqvist, 1998Granqvist, , 2002Jennings, Stoker, & Bowers, 2009;Valentino & Sears, 1998). Children and adolescents adopt their parents' political and religious orientations to a certain degree, and this early parental transmission appears to influence the character of later adult religious or political development even though direct parental influences often appear to decrease with offspring age (e.g., Francis & Brown, 1991;Jennings et al, 2009;Myers, 1996).…”
Section: Socialization Perspectivesmentioning
confidence: 99%
“…Campaigns exert this effect by promoting learning and activation. Campaigns help citizens learn because more people come into contact with political ideas and information in the months preceding an election than at any other time in the 4-year election cycle (e.g., Sears & Valentino, 1997;Valentino & Sears, 1998). Campaigns also activate latent preferences-because they culminate in an important decision that encourages citizens to use the information they receive (Campbell, Converse, Miller, & Stokes, 1960), and because existing preferences may themselves become stronger as campaigns provide more information to support them (Lodge & Taber, 2013;Tesser, 1978).…”
Section: The Current Study: How Political Preferences Change As a Fmentioning
confidence: 99%